Regionalization Studies for Municipal Solid Waste Management in Brazil - Pimentel Gómes, Aline; Prietto, Pedro; Locatelli Kalil, Rosa Maria; Pandolfo, Adalberto; Reyes-Corredera, Sergio Jesús (Indercience, 2024)
Municipal solid waste (MSW) management at the regional level has become increasingly important over the last years. The regionalisation studies evaluate ideal arrangements of municipalities to constitute consortia for sharing infrastructure and management. A document analysis of regionalisation studies for MSW management from 18 Brazilian states was made in order to identify and evaluate the shape of the regions, the criteria and the methods used. The results evidenced a big difference regarding the number of regions proposed, the number of municipalities, the area and population of each region, the environmental, economic, social and political criteria, the hierarchy and the tools used. There is a lack of standardisation in the elaboration of these studies and the development of a consistent method, with the definition of hierarchical criteria, the use of appropriate geospatial tools, as well as the social participation in the decision-making process can contribute to the elaboration of regionalisation studies.
Keywords: Residuos; Municipal solid waste; MSW; Waste management; Regionalisation for waste management; Public consortia; Brazil